Analysis Of User Experience Of ChatGPT And Gemini Users Using The User Experience Quistionnaire (UEQ) For Education - Nasrul, Ilham; Angraini, Angraini; Hamzah, Muhammad Luthfi; Saputra, Eki (ISB Atma Luhur, 2024)
AI is becoming more and more crucial in the digital age to support kids in overcoming obstacles to learning and succeeding academically. The use of chatbots is one example of AI progress. Two well-known chatbots are Gemini and ChatGPT. Because they are useful and support a variety of learning tasks, including answering questions, producing articles, expanding knowledge, and other academic activities, both applications are highly well-liked and preferred by students. By using a case study on the Facebook community with the number of samples needed in this study as many as 377 respondents based on the Krejcie and Morgan formula, The purpose of this study was to determine whether user experiences with different applications differed. User experience measurement was carried out using the User Experience Questionnaire (UEQ) approach on the variables of Efficiency, Novelty, Attractiveness, Stimulation, Perspicuity, and Dependability. The results of the study show that all user experience variables for the ChatGPT and Gemini applications received poor ratings, and there were no significant differences in any of these variables. However, based on UEQ measurements, it was found that both applications received better scores on the stimulation and novelty variables, while the attractiveness, clarity, efficiency, and accuracy variables received poor results. To improve user experience in the ChatGPT and Gemini applications, the quality of all variables needs to be enhanced.